P365 Upsurge of Mucormycosis in COVID-19—a retrospective study in a tertiary care hospital in Punjab. (20th September 2022) - Mohan, Sangeetha
Abstract: Poster session 3, September 23, 2022, 12:30 PM - 1:30 PM:   Objectives: Coronavirus disease 2019 (COVID-19), caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has been linked to a variety of opportunistic bacterial and fungal infections. Mucorales have been reported as the main fungal pathogens to exist as co-infection with COVID-19. Factors that contribute to a higher incidence of Mucormycosis or Mucorales to germinate in COVID-19 patients are high glucose levels in their blood (diabetes, steroid-induced hyperglycemia), low oxygen content (hypoxia), high iron levels, and decreased phagocytic activity of neutrophils due to immunosuppression because of cytokine storm in SARS-CoV-2 infection. Mucormycosis is an angioinvasive disease caused by order Mucorales and genus Rhizopus, Mucor, Rhizomucor, Cunnighamella, and Lichthemia . The most common species amongst all is Rhizopus arrhizus which is responsible for 90% cases of Rhino-Orbital Cerebral form and accounts for 60% cases of mucormycosis cases in India. Methods: A retrospective study was conducted at Christian Medical College and Hospital, Ludhiana from May 1, 2021 to February 28, 2022 for a duration of 10 months. Most of the samples obtained were necrotic bone/tissue or mucosa from the rhino-cerebral part. The obtained sample was inoculated on Sabouraud's Dextrose Agar (SDA) at 22 ° C as well as 37 ° C followed by 40% KOH examination. The tubes were routinely checked once in a week and Lactophenol Cotton Blue (LPCB) preparation was made from teasing the isolate once it becomes culture positive. Results: Total 29 samples were smear-positive for broad, sparsely septate hyphae in KOH examination under the microscope. Out of those 29 cases, 18 (62.06%) patients were COVID-19 positive (either RTPCR positive, TrueNat PCR positive, or Rapid Antigen positive), 5 patients were COVID-19 negative and COVID-19 testing was not done in 6 patients. Out of 29 smear-positive cases, 17 (58.62%) were culture positive for Mucorales, 7 (24.13%) grew contaminants namely Aspergillus species (mainly Aspergillus flavus ), Penicillium species, bacterial contamination, and 5 (17.24%) were culture negative. Amongst 17 cases of Mucorales, 9 (52.94%) were Rhizopus species, 6 (35.29%) were Mucor species and 2 (11.76%) were Rhizomucor species. Amongst the culture-positive cases for Mucorales, 13 (72.22%) cases were COVID-19 positive. Conclusion: COVID-19 has thrown the entire globe into chaos, and there is still no specific cure for this viral illness. Patients are susceptible to secondary fungal infections such as Mucormycosis as a result of the infection, immunosuppression, previous comorbidities, and medicines. Mucormycosis infection is severe because of its rapid disease progression and angioinvasive nature. As a result, researchers and healthcare practitioners should take immediate steps to control this mucormycosis infection by understanding its impact and severity, particularly in COVID-19 patients. A multidisciplinary approach should involve quick diagnosis, antifungal therapy, any surgical consultation, and treatment that may help to reverse the underlying disease.